Fortalecimiento del Core para la prevención de pubalgia en futbolistas - Caisabanda Chango, Julissa Johanna (2022)
ABSTRACT: This research work aims to address the benefits of strengthening the core as physiotherapeutic treatment for the prevention of pubalgia in soccer players. Pubalgia is described as groin pain characterized by overuse and is a common problem among athletes, especially in those sports that involve running, kicking, and changing direction. Core strengthening is effective in preventing injuries, this causes a reduction in the risk of injury to both the lower and upper limbs. As far as football is concerned, it is considered essential to achieve optimal performance of the footballer. The prevention of pubalgia in the country is scarce due to the lack of knowledge of the benefits that this technique has on soccer players, however, 85 scientific articles were analyzed, which through the exclusion criteria and the evaluation of the Pedro scale were 35 articles were selected, in turn based on a minimum score of 6 using the PEDro scale, the original articles were found in languages such as English, Spanish and Portuguese. The databases that were used to obtain the information for the present work were PubMed, Scielo, Elsiever, Journal of orthopedic and sports physiotherapy and Sports Medicine. At the conclusion of the research, with the analysis of each of the scientific articles, it has been possible to meet the objective set by demonstrating that strengthening the core as such is an effective, safe method, helping to prevent injuries in athletes with Pubalgia caused by a muscle imbalance, fatigue, poor posture and abdominal wall deficiencies, thus improving athletic performance.